Polysemy of the Term "Information and Communication Culture" - E. M. Shevchik-Giris (Цифровая трансформация)
The article discusses the content of the term "information and communication culture". A definition of the term is given from the viewpoint of cultural studies, pedagogy, sociology, computer science, psychology and medicine. Also it is proposed author’s definition of the term.